2016
DOI: 10.1038/oncsis.2016.60
|View full text |Cite
|
Sign up to set email alerts
|

ZEB1 induces EPB41L5 in the cancer mesenchymal program that drives ARF6-based invasion, metastasis and drug resistance

Abstract: Onset of the cancer mesenchymal program is closely associated with cancer malignancy and drug resistance. Among the different epithelial–mesenchymal transition (EMT)-associated transcriptional factors, ZEB1 has a key role in inducing the mesenchymal phenotypes and stem cell-like properties of different breast cancer cells. ARF6 and its effector AMAP1 are frequently overexpressed in breast cancer cells, and promote invasion, metastasis and drug resistance. EPB41L5 is induced during EMT, and mediates the disrupt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
57
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 56 publications
3
57
1
Order By: Relevance
“…Consistently, we have shown that ZEB1 is central in inducing EPB41L5 in breast cancer cells and renal cancer cells [16, 18]. However, analysis of The Cancer Genome Atlas (TCGA) RNA-Seq datasets on human primary tongue SCCs showed that ZEB1 mRNA levels do not statistically correlate with EPB41L5 mRNA levels (Fig.…”
Section: Resultssupporting
confidence: 66%
See 4 more Smart Citations
“…Consistently, we have shown that ZEB1 is central in inducing EPB41L5 in breast cancer cells and renal cancer cells [16, 18]. However, analysis of The Cancer Genome Atlas (TCGA) RNA-Seq datasets on human primary tongue SCCs showed that ZEB1 mRNA levels do not statistically correlate with EPB41L5 mRNA levels (Fig.…”
Section: Resultssupporting
confidence: 66%
“…We have previously shown that silencing of EPB41L5 in other types of cancers, such as breast cancer and renal cancer, drastically improves their drug-resistance [16, 18]. We hence examined whether the same is the case with SCC-9 cells.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations